O papel do controle de armas de fogo sobre os homicídios - Siqueira, Rogério Moreira de (2022)
There are strong controversies about the effects of firearms availability in relation to a number of criminal variables. These controversies are directly proportional to the various methodological challenges that researchers need to overcome in order not to resolve their results. In Brazil, a gun control policy evolves from an almost total absence of control mechanisms to a centralized and quite restrictive model, however, the indicators of violent deaths with the use of firearms do not respond in the same way. An extension of Becker (19) is proposed to take and deter the limits of the model8 legally composite availability of available weapons over self-defense and deterrence of available weapons. Given the theoretical ambiguity of these effects, the main objective is to empirically verify the influence of firearms that legally entered into circulation as well as the entry into force of the Disarmament Statute on lethal armed violence. For this purpose, data on firearm homicides of the total population and of young blacks from SIM/DATASUS and weapons obtained from SINARM/PF for a sample of Brazilian states from 1997 to 2015 are used. The dynamics of homicides between states are used as controls that the specialized literature highlights as determinants of crime whose sources come from IBGE, IPEA, SICONFI/STN, INEP/MEC. The data form an exclusive panel and are estimated by the GMM method in a system based on the contributions of Arellano eBover (1995) and Blundell and Bond (1998). The results of the fireworks project, however, increased among blacks. On the other hand, those that legally entered into circulation on the side not protected by significant weapons with this instrument.